2012
DOI: 10.1016/j.cpr.2012.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Self-help treatment of anxiety disorders: A meta-analysis and meta-regression of effects and potential moderators

Abstract: Self-help treatments have the potential to increase the availability and affordability of evidence-based treatments for anxiety disorders. Although promising, previous research results are heterogeneous, indicating a need to identify factors that moderate treatment outcome. The present article reviews the literature on self-help treatment for anxiety disorders among adults, with a total sample of 56 articles with 82 comparisons. When self-help treatment was compared to wait-list or placebo, a meta-analysis ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 194 publications
(219 reference statements)
5
79
0
Order By: Relevance
“…The results indicated patients without a comorbid depressive disorder had better outcomes from FtF-CBT compared to guided self-help, but there were no differences in the outcome between the two treatment conditions for patients with a comorbid depression. Previous research results are equivocal but indicate a trend toward a negative association between depression and outcome for both guided self-help and face-to-face CBT for anxiety disorders (Allen et al, 2010;Brown et al, 1995;Chambless et al, 1997;Eskildsen et al, 2010;Hedman et al, 2012;McCabe & Gifford, 2008;Nordgreen et al, 2012;Nordgreen et al, 2010). We did find a similar effect on the self-reported outcome for the Immediate FtF-CBT condition but not for guided self-help, and as mentioned only differences in effect of the treatments among the patients with no comorbid depression.…”
Section: Discussionsupporting
confidence: 41%
See 3 more Smart Citations
“…The results indicated patients without a comorbid depressive disorder had better outcomes from FtF-CBT compared to guided self-help, but there were no differences in the outcome between the two treatment conditions for patients with a comorbid depression. Previous research results are equivocal but indicate a trend toward a negative association between depression and outcome for both guided self-help and face-to-face CBT for anxiety disorders (Allen et al, 2010;Brown et al, 1995;Chambless et al, 1997;Eskildsen et al, 2010;Hedman et al, 2012;McCabe & Gifford, 2008;Nordgreen et al, 2012;Nordgreen et al, 2010). We did find a similar effect on the self-reported outcome for the Immediate FtF-CBT condition but not for guided self-help, and as mentioned only differences in effect of the treatments among the patients with no comorbid depression.…”
Section: Discussionsupporting
confidence: 41%
“…Some studies have indicated that lower age and longer duration of the disorder (Nordgreen et al, 2010) and the presence of cluster C personality disorders (Andersson, Carlbring, & Grimund, 2008) are associated with a worse outcome of ICBT for PD. Hedman et al (2012) reported that comorbid anxiety and depression were related to a worse outcome of ICBT for SAD, whereas another study did not find this association (Nordgreen et al, 2012). Thus, the most consistent findings in the research literature on non-specific predictors indicate that patients with more intense primary symptoms and comorbid disorders have a poorer end state from FtF-CBT of PD and SAD, but the results are in general equivocal and inconclusive, particularly for predictors of improvement from treatment.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Key positive points included; easy to read, author understands with compassion, practical steps provided, includes real vignettes or interviews, and author has been through anxiety. Bibliotherapy can be almost as effective as face-to-face therapy with a counsellor or psychologist 63 and should therefore be more cost effective than a programme with intensive face-to-face contact. Also, the self-help format allows practitioners to access help without losing clinical time.…”
Section: Bibliotherapymentioning
confidence: 99%